2016
DOI: 10.1177/0163278716652217
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Follow-Up of a Sexual Health Promotion Program for Spanish Adolescents

Abstract: The aim is to evaluate the effects of the Competencias para adolescentes con una sexualidad saludable (COMPAS) program and compare them with an evidence-based program ( ¡Cuídate!) and a control group (CG). Eighteen public high schools were randomly assigned to one of the three experimental conditions. Initially, 1,563 Spanish adolescents between 14 and 16 years of age participated, and 24 months after their implementation, 635 of them completed a survey. Self-report measures collected data on sexual behavior, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 27 publications
1
42
1
4
Order By: Relevance
“…In our study, consistent use of condoms (22%) was less frequent than in other studies conducted in Colombia (30%) [16] and internationally (40–54%) [27, 28]. Navarro and Vargas [29] found that 82.1% of a sample of adolescents from Barranquilla, Colombia, used condoms occasionally.…”
Section: Discussioncontrasting
confidence: 68%
“…In our study, consistent use of condoms (22%) was less frequent than in other studies conducted in Colombia (30%) [16] and internationally (40–54%) [27, 28]. Navarro and Vargas [29] found that 82.1% of a sample of adolescents from Barranquilla, Colombia, used condoms occasionally.…”
Section: Discussioncontrasting
confidence: 68%
“…Therefore, the use of condoms must be promoted in order to prevent STIs and unplanned pregnancies [1, 2, 4, 7]. A recent study in Colombia showed that only 22% of adolescents (14–19 years old) were using condoms consistently [8]; this percentage differs from Colombian data for previous years (30 to 42%) [9, 10] and from data obtained in other countries (40 to 54%) [11, 12]. These figures highlight the need to look for alternatives to the male condom in order to counteract its decreasing use.…”
Section: Introductionmentioning
confidence: 99%
“…Young people have to learn about sexuality, STI and contraception [ 3 , 14 ]. However, studies show that receiving the information is not always related to adequate sexual and contraceptive attitude and more effective strategies of behavioral change in individuals who engage in sexual activity are needed [ 15 , 16 ]. On the other hand, information is not synonymous of a healthy lifestyle.…”
Section: Introductionmentioning
confidence: 99%